Related Rules Study of Gear Web Structure and Gear Tooth Root Crack Propagation based on Extended Finite Element Method - Xu Detao; Tang Jinyuan; Zhou Wei; Xu Yongli (Jixie chuandong)
The extended finite element method（ XFEM） is investigated to calculate gear crack propagation. The crack propagation computer program are developed,and the correctness is verified with the aid of standard examples. The distance between crack propagation path and gear center as the evaluation indicator of tooth / rim fracture is proposed,the effect of rim thickness,web thickness,sizes and positions of web holes on spur gear tooth crack propagation path is investigated. The results indicate that,the decrease of rim thickness results in gear tooth crack propagation paths moving down to gear center integrally,which increases the occurrence of rim fracture. The decrease of web thickness results in gear tooth crack propagation paths moving down to gear center integrally,which increases the occurrence of rim fracture. The existence of web holes increases the occurrence of rim fracture and the larger is the hole,the greater is the occurrence. The preferred position of web hole lies in vertically below the tooth socket.